Tumor lysis syndrome following cabazitaxel administration for metastatic castration‐resistant prostate cancer: A case report. Issue 4 (15th April 2019) - Oshima, Masashi; Mayumi, Shozaburou; Yazaki, Kai; Nakamura, Yuuki; Konishi, Tsuzumi; Saito, Kimitoshi; Washino, Satoshi; Miyagawa, Tomoaki
Abstract : Introduction: Tumor lysis syndrome is a rare and potentially fatal complication of oncological treatment. It is characterized by biochemical changes associated with the rapid lysis of malignant cells, usually after chemotherapy. Tumor lysis syndrome is typically noted in patients with hematological malignancies, and it rarely occurs in patients with solid tumors. Case presentation: We report a case of tumor lysis syndrome after cabazitaxel administration for metastatic castration‐resistant prostate cancer. To our knowledge, tumor lysis syndrome after cabazitaxel therapy has not been reported previously. The patient was a 77‐year‐old man who developed clinical tumor lysis syndrome after a single dose of cabazitaxel for metastatic castration‐resistant prostate cancer. He was treated with hydration and the recombinant uricolytic agent rasburicase, and his condition improved. Conclusion: It is extremely important to assess the risk factors for tumor lysis syndrome and to perform active prevention procedures in order to avoid fatal outcomes. It may be beneficial to use rasburicase in patients with established tumor lysis syndrome.